The remember response : Subject to bias, graded, and not a process-pure indicator of recollection - ROTELLO, Caren M; MACMILLAN, Neil A; REEDER, John A; WONG, Mungchen (Psychonomic bulletin & review, 2005)
Recognition memory judgments have long been assumed to depend on the contributions of two underlying processes: recollection and familiarity. We measured recollection with receiver-operating characteristic (ROC) data and remember-know judgments. Under standard remember-know instructions, the two estimates of recollection diverged. When subjects were told they might need to justify their remember responses to the experimenter, the two estimates were more likely to agree. The data support the conclusion that remember responses are generally based on a continuous underlying process but that specific task instructions can produce data that appear consistent with a high-threshold recollective process. Models based on signal detection theory provide a better account of these data than does the dual-process model (Yonelinas, 1994) or process-pure interpretations.